Pengaruh Service Quality dan Customer Trust terhadap Customer Loyalty melalui Customer Satisfaction pada Pengguna E-Wallet - Teuku Rio Febrian Alfa Risky; Osly Usman; Ayatulloh Michael Musyaffi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the influence of service quality and customer trust on customer satisfaction and customer loyalty among DANA e-wallet users in DKI Jakarta, both directly and indirectly through customer satisfaction as a mediating variable. Data were collected from 235 respondents through an online questionnaire and analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach. The results indicate that service quality and customer trust have a positive and significant effect on customer satisfaction. However, neither variable has a significant direct effect on customer loyalty. Conversely, customer satisfaction shows a positive and significant influence on customer loyalty and serves as a mediator between service quality and customer trust toward customer loyalty. The instrument's validity and reliability were confirmed through outer model testing, discriminant validity, and construct reliability analysis. These findings highlight the critical role of customer satisfaction in building user loyalty toward e-wallet services.